The ups and thrusts in the earth's crust of the Kirovograd ore region and the connection with them of uranium mineralization - O.B. Gintov; S. V. Mychak (Геофизический журнал, 2012)
In accordance with the data of tectonophysical studies of a set of uranium deposits of the central part of the Ukrainian shield it was shown that those deposits were formed on the stage of compression of the Earth's crust between two stages of stretching. The stretching prevented through passage of ore solutions to the day surface above the surface of erosion. In this case the structures of uplifts type with hanging flanks that served as a screen for ore solutions were formed. Ore mineralization was mainly concentrated in ruptures with oblique bedding (thrust faults) and were kinamatically conjugated with thrusts.